INCLUSIVE BANKING SERVICE TRANSFORMATION STRATEGY TO INCREASE CUSTOMER LOYALTY AT BRI SIDOARJO BRANCH - Fadli Arwan , Dio; Sholichah , Nihayatus; Patria W , Dandy; Devy Pramudiana, Ika (International Journal of Multidisciplinary Reseach, 2025)
This study explores public and financial service dynamics in Sidoarjo Regency through two lenses: flood mitigation in Krian District and inclusive banking at Bank BRI. Both sectors face challenges in transitioning from rigid frameworks to adaptive, human-centric ecosystems. Methodologically, this research employs a qualitative descriptive approach. In the first context, findings indicate that synergy between the Environmental Office (DLH) and Disaster Management Agency (BPBD) is rooted in trust-building and data transparency. However, systemic hurdles like budgetary rigidity and jurisdictional ambiguity regarding central government rivers (BBWS) hinder optimal resource sharing. Parallelly, Bank BRI Sidoarjo enhances customer loyalty through "hybrid banking," integrating digital efficiency with high-touch human interaction. The roles of "Mantri" and "Digital Advisors" create emotional loyalty, proving that empathy remains vital amidst digitalization. Both studies conclude that technological advancement reaches peak effectiveness only with institutional frameworks prioritizing human empathy and integration. The research recommends formalizing integrated SOPs and issuing local regulations, such as a Regent Regulation, to provide a legal umbrella for administrative flexibility. This ensures sustainable, inclusive service delivery for the Sidoarjo community.